Financial Inclusion in Ethiopia : Key Findings from the Ethiopia Socioeconomic Survey 2018/19 - Achew, Mengistu Bessir; Ambel, Alemayehu A.; Gradstein, Helen L.; Tsegay, Asmelash Haile; Ul Haq, Imtiaz; Varghese, Minita M.; Yonis, Manex Bule (World Bank, Washington, DC, 2021)
Integrating a financial inclusion module into a multitopic household survey like the Ethiopia Socioeconomic Survey (ESS) makes it possible to explore how different community spatial, demographic, and socioeconomic characteristics affect the financial decisions of individuals and households. In addition, the survey data underpins financial inclusion policymaking and measurement, an agenda spearheaded by the National Bank of Ethiopia through the National Financial Inclusion Strategy (NFIS) efforts. The survey collected information from households and individuals on several financial matters including current levels of access to finance based on the prevalence of account ownership, use of financial services, types of institutions used, and their proximity to the household; household and individual financial decisions about savings, credit, insurance, and payments; and financial behavior, knowledge, and attitudes. The data provides a rigorous, multidimensional picture of where the country stands in expanding access to formal financial services and reaching the NFIS goals. This brief summarizes the ESS Financial Inclusion survey report, emphasizing on key findings on account ownership, gender gap, financial behavior and knowledge of financial institutions and products.